Al-Fārābī and his school - Netton, Ian Richard (Arabic thought and culture., 1992)
Examines one of the most exciting and dynamic periods in the development of medieval Islam, from the late 9th to the early 11th century, through the thought of five of its principal thinkers, prime among them al-Farabi. This great Islamic philosopher, called 'the Second Master' after Aristotle, produced a recognizable school of thought in which others pursued and developed some of his own intellectual preoccupations. Their thought is treated with particular reference to the most basic questions which can be asked in the theory of knowledge or epistemology. The book thus fills a lacuna in the l.